Health and Safety Concerns after the Gen Z Movement in Nepal - Adhikari, Ram Hari (Journal of Health Promotion, 2025)
Fire incidents and civil unrest are emerging threats to human safety, health, and social stability in low-income countries, including Nepal. This article critically examines the health and safety concerns emerged with Gen Z movement in Nepal (September 2025), which began as a youth-led protest and escalated into violent unrest and widespread fires. The movement resulted in deaths, injuries, and destruction of public and private property, which reveals weaknesses in governance, public safety management, and mental health support systems. Drawing from national reports and international studies, this paper explores the health, safety, and psychosocial implications of the movement and the lessons it gives for policymakers, health educators, and communities. It concludes that integrated, evidence-based strategies combining preventive education, mental health interventions, digital literacy, and transparent governance are vital to fostering a culture of safety and resilience in Nepal.